Bodv scars in imprisoned women victimized by physical violence and vulnerability to STD-Aids - Giordani, Annecy T.; Bueno, Sônia M.V. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Background: Women have been victimized by violence in both private and public spaces. In prisons, they also experience physical and moral mistreatment, extortion, abuse and sexual harassment. In this setting, they are exposed to risks, including HlV-aids and STD infection. Objectives: To investigate their perception of violence by detecting their possible experiences and taking into account their body scars caused by aggression with or without arms aiming at identifying risks of STD-aids. Methods: A humanistic and qualitative action-research was developed according to ethical precepts and scientific rigor. The subjects' accounts were recorded on cassette tapes and later transcribed. Photographs of their scars were taken. Their perception and problems related to violence and risks of STD-aids were identified by means of an exploratory study conducted after the intervention. Nine prisoners from two women’s public prisons in the interior of São Paulo State were studied. Results: All of them presented traumatic body scars resulting from physical violence caused by firearms and/or cutting instruments, totaling 12 lesions. Most of them were single mothers aged 18 to 34 years old, unemployed and had poor education. They had had the scars for I to 11 years which had been produced in and out of the prison by known and unknown aggressors as a result of jealousy and fights. Conclusion: The women felt deeply disrespected and abused in and out of prison by numerous deprivations and humiliations to which they had been submitted. Their accounts denoted trauma, unconformity, anger and revolt. All of them were aware of their vulnerability to STD and HlV-aids. particularly due to sexual abuse.